Burn Wound Microbiology and the Antibiotic Susceptibility Patterns of Bacterial Isolates - Hina Faisal, Amber Yasmeen Alvi, Marvi, Syed Zakir Hussain Shah, Hidayatullah Memon, Samina Tarique, Fahim Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Burn wounds are prone to infections, which significantly impact patient outcomes. The microbiological profile of burn wounds and the antibiotic susceptibility patterns of the bacterial isolates play a crucial role in managing infections and preventing complications. Objective: To identify the bacterial pathogens responsible for burn wound infections and assess their antibiotic susceptibility patterns. Methodology: This cross-sectional study was conducted at Sir Syed College of Medical Sciences for girls between during January 2022 to December 2022. including 125 pediatric patients diagnosed with burn wound infections. Results: The study found that Pseudomonas aeruginosa (30%) and Staphylococcus aureus (25%) were the most common bacterial isolates in burn wounds, with high resistance to ciprofloxacin (70%) and penicillin (60%). The average hospital stay was 15.6 days, with longer stays for severe infections. Complications like sepsis (9.6%) and organ failure (4%) were more frequent in the surgical group. Most patients (90%) had normal urinary function, and 70% returned to normal activities within 4 weeks. Conclusion: The study highlights the diverse microbiological profile of burn wound infections and the high prevalence of antibiotic-resistant bacteria. Effective antibiotic stewardship and regular monitoring of resistance patterns are essential for improving patient outcomes in burn care. Keywords: Burn wounds, microbiology, bacterial isolates, antibiotic resistance, Pseudomonas aeruginosa, Staphylococcus aureus, Klebsiella pneumoniae.